Development of Web Based Pharmacy Inventory System: Pembangunan Sistem Inventori Farmasi Berasaskan Web - Misran, Nur Shafikah; Mohmad Hassim, Dr. Yana Mazwin (Applied Information Technology And Computer Science, 2022)
Nowadays, pharmacy management system is one of the most widely used methods in pharmacy stores. It is also used to handle pharmacy related operations such as inventory of products, sales operations, record keeping, products stock and expired product management. Many pharmacies still do not have their own web-based pharmacy management system that can cover all activities automatically. As example, even when the pharmacy already has their own software, but they still need to check the expired date and number of stock manually. It needs the pharmacist themselves to check the expired date at least twice a week and it can take a lot of time to find out whether certain medicines are out of stock. This project offers insight into the development and implementation of a web-based pharmacy management system. The main goal is so that it can improve the efficiency of the system and give more convenience to the pharmacist. This system is designed to overcome all the problems that related to the existing system. For the pharmacy shops, this web-based pharmacy management system has its own importance because it can monitor all transactions made at regular sales, identify all staffs, admins, customers, balance stock, product expiry date and others. All tasks around the pharmacy shop that can improve efficiency and increase profit will be handled.